A Highly Efficient Heterogeneous Copper-Catalyzed Oxidative Cyclization of Benzylamines and 1,3-Dicarbonyl Compounds To Give Trisubstituted Oxazoles - Wei, Li; You, Shengyong; Tuo, Yuxin; Cai, Mingzhong (Synthesis, 2019)
The heterogeneous copper-catalyzed cascade oxidative cyclization between benzylamines and 1,3-dicarbonyl compounds was achieved by using the 3-(2-aminoethylamino)propyl-functionalized MCM-41-immobilized copper(II) complex [MCM-41-2N-Cu(OAc)2] as catalyst and t-BuOOH (TBHP) as oxidant, with iodine as additive, under mild conditions, yielding a wide variety of 2,4,5-trisubstituted oxazoles in mostly good to excellent yields. This heterogeneous copper catalyst can be facilely prepared via a simple two-step procedure from readily available and inexpensive reagents and exhibits a slightly higher activity than Cu(OAc)2. MCM-41-2N-Cu(OAc)2 is also easy to recover and can be recycled up to eight times with almost consistent activity. The reaction is the first example of heterogeneous copper-catalyzed intermolecular cyclization for the construction of polysubstituted oxazoles.
Keywords: copper; 2,4,5-trisubstituted oxazole; oxidative cyclization; heterogeneous catalysis; cascade reaction